Sustainable feedstock potential – a limitation for the bio-based economy?. (1st June 2016) - Hennig, Christiane; Brosowski, André; Majer, Stefan
Abstract: Within the debate and research of the transition towards a bio-based economy a shortfall in considering and evaluating the actual available sustainable biomass potential for realizing this emerging concept can be noted. This paper provides insights into the role of feedstock availability and provision in particular addressing the current scientific discussion on the availability and cost provision of biomass resources in the context of energy production, and the implications for the technological concepts, mainly biorefineries. A lack of a harmonized methodological approach covering minimum requirements for determining biomass potentials can be seen. This does not allow a comparison and aggregation of the data for receiving a bigger picture on the feedstock potential. Consequently, academia and decision makers may not take a final position on the possible magnitude of an emerging bio-economy at the moment. The presented examples also reveal that a more distributed production might allow developing a larger share of the available biomass potential. Highlights: Development of a bioeconomy is linked to a sound knowledge on biomass availability. Establishment of minimum requirements for transparency of biomass potential results. Global biomass potential is limited asking for intelligent utilization strategies.